Best Paper Selection (Yearbook of Medical Informatics, 2021)
Fabregat A, Magret M, Ferré JA, Vernet A, Guasch N, Rodríguez A, Gómez J, Bodí M. A Machine Learning decision-making tool for extubation in Intensive Care Unit patients. https://www.sciencedirect.com/science/article/abs/pii/S0169260720317028?via%3DihubKempa-Liehr AW, Lin CYC, Britten R, Armstrong D, Wallace J, Mordaunt D, O’Sullivan M. Healthcare pathway discovery and probabilistic machine learning. https://www.sciencedirect.com/science/article/abs/pii/S1386505619308068?via%3DihubLi Y, Nair P, Lu XH, Wen Z, Wang Y, Dehaghi AAK, Miao Y, Liu W, Ordog T, Biernacka JM, Ryu E, Olson JE, Frye MA, Liu A, Guo L, Marelli A, Ahuja Y, Davila-Velderrain J, Kellis M. Inferring multimodal latent topics from electronic health records. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7242436/Weemaes M, Martens S, Cuypers L, van Elslande J, Hoet K, Welkenhuysen J, Goossens R, Wouters S, Houben E, Jeuris E, Jeuris K, Laenen L, Bruyninckx K, Beuselinck K, André E, Depypere M, Desmet S, Lagrou K, Van Ranst M, Verdonck AKLC, Goveia J. Laboratory information system requirements to manage the COVID-19 pandemic: A report from the Belgian national reference testing center. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7197526/